Acetone Iodination Kinetics in Flow with Online UV Monitoring and Continuous Control. Issue 17 (6th May 2019) - Yao, Xingjun; Deng, Qiulin; Wang, Shuhao; Wang, Wei; Hou, YIxin; Gao, Zhibin; Wu, Yingshuang; Guo, Zengjing
Abstract: Kinetics of acetone iodide synthesis was investigated in a microchannel reaction system mainly composed of a micromixer and a tubular reactor. This system can be used as a plug flow reactor, as proved by the low variance (0.006) of residence time distribution detected by a step stimuli–response tracer. An online ultraviolet monitoring system was built to fast and reliably detect the transmittance of the flowing solution. Reaction kinetics was tested at different reactant concentrations and temperatures (35‐50 °C). Second‐order kinetics concerning acetone and HCl was identified with activation energy of 67.86 kJ/mol. Abstract : Schematic diagram of apparatus mainly composed of a micromixer and a tubular reactor for kinetic research of acetone iodide synthesis. This system can be used as a plug flow reactor, as proved by the low variance of residence time distribution detected by a step stimuli–response tracer. An online ultraviolet monitoring system was built to fast and reliably detect the transmittance of the solution.